2020
DOI: 10.1002/path.5468
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtyping reveals immune alterations in IDH wild‐type lower‐grade diffuse glioma

Abstract: Isocitrate dehydrogenase (IDH) wild‐type diffuse lower‐grade glioma (LGG) is usually associated with poor outcome, but there have been disputes over its clinical outcome and classification. We present here a robust gene expression‐based molecular classification of IDH wild‐type diffuse LGG into two subtypes with distinct biological and clinical features. A discovery cohort of 49 IDH wild‐type diffuse LGGs from the Chinese Glioma Genome Atlas (CGGA) was subjected to clustering and function analysis. Seventy‐thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 54 publications
4
40
0
Order By: Relevance
“…Previous studies [ 10 , [22] , [23] , [24] ] pointed out that tumor-infiltrating immune cells have emerged as a key regulator of tumor growth and progression in LGG. Tumor-infiltrating immune cells are part of the complex microenvironment and are associated with the biological behavior and patient survival in LGG [ [25] , [26] , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [ 10 , [22] , [23] , [24] ] pointed out that tumor-infiltrating immune cells have emerged as a key regulator of tumor growth and progression in LGG. Tumor-infiltrating immune cells are part of the complex microenvironment and are associated with the biological behavior and patient survival in LGG [ [25] , [26] , [27] , [28] , [29] ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we performed a comprehensive meta-analysis to assess the overall prognostic significance of ARL9 using data from four public databases. Moreover, as substantial attention has been focused on the crucial role of the immune microenvironment in the progression of LGG [ [10] , [11] , [12] , [13] ], we also mined Tumor Immune Estimation Resource (TIMER) database to evaluate the potential correlation between ARL9 and immune infiltration levels in LGG. Finally, we examined the biological processes of ARL9 in which ARL9 is involved through gene enrichment analysis, to study the functional mechanism of ARL9 in LGG.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies have found that tumour-in ltrating immune cells play an important role in the progression and development of cancer [24][25][26][27]. Few studies have pointed out the relationship between EMILIN2 and immune in ltration.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Using R package ‘ConsensusClusterPlus’, consensus clustering was performed for class discovery based on the comparison of alternative splicing profile 21‐23 . Measured by median absolute deviation (MAD > 0.16), the most variable AS events were retained for subsequent clustering.…”
Section: Methodsmentioning
confidence: 99%